2005
DOI: 10.1128/iai.73.10.6601-6607.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibody Response to Outer Membrane Protein G1a, a Lipoprotein of Moraxella catarrhalis

Abstract: Moraxella catarrhalis is an important cause of respiratory infections in adults with chronic obstructive pulmonary disease (COPD) and of otitis media in children. Outer membrane protein (OMP) G1a is an ϳ29-kDa surface lipoprotein and is a potential vaccine candidate. The gene that encodes OMP G1a was expressed and purified using a novel plasmid vector. [ 3 H]palmitic acid labeling demonstrated that both native and recombinant OMP G1a contain covalently bound palmitic acid. To assess the expression of OMP G1a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
2
17
1
Order By: Relevance
“…Variability among individuals in the surface bacterial antigens to which antibodies are directed is a hallmark of antibody responses to bacteria in the COPD setting (9,44,45). The proportion of patients who developed new antibody responses to Msp22, Msp75, and Msp78 observed in this study parallels the proportion observed for M. catarrhalis OMPs E, G1a, and G1b when similar methods were used (2,3,11). The observation that some patients with COPD developed new systemic and mucosal antibodies to Msp22, Msp75, and Msp78 in samples collected 1 month after clearance of M. catarrhalis compared to paired samples collected immediately before acquisition of the organism supports the conclusion that the proteins are expressed by M. catarrhalis in the human respiratory tract.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Variability among individuals in the surface bacterial antigens to which antibodies are directed is a hallmark of antibody responses to bacteria in the COPD setting (9,44,45). The proportion of patients who developed new antibody responses to Msp22, Msp75, and Msp78 observed in this study parallels the proportion observed for M. catarrhalis OMPs E, G1a, and G1b when similar methods were used (2,3,11). The observation that some patients with COPD developed new systemic and mucosal antibodies to Msp22, Msp75, and Msp78 in samples collected 1 month after clearance of M. catarrhalis compared to paired samples collected immediately before acquisition of the organism supports the conclusion that the proteins are expressed by M. catarrhalis in the human respiratory tract.…”
Section: Resultssupporting
confidence: 69%
“…To determine the cutoff value for a significant change between preacquisition and postclearance serum IgG and sputum IgA levels, 10 control pairs were examined using a previously described method (2,3,34,36). Control samples obtained 2 months apart (the same time interval used for the experimental samples) from patients whose sputum cultures were negative for M. catarrhalis were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, antibodies to conformational epitopes that are denatured in SDS-PAGE will not be detected. Indeed, in other work using quantitative enzyme-linked immunosorbent assays with purified recombinant protein antigens, we have demonstrated the development of sputum IgA to other surface proteins of M. catarrhalis, including outer membrane proteins CD and G1a (1,16). Sputum IgA to these antigens was not detected by immunoblot assay in the present study, indicating the development of antibodies to conformational epitopes on the proteins.…”
Section: Discussioncontrasting
confidence: 38%
“…Cloning of the oppA gene. The pCATCH plasmid is an expression vector engineered to express recombinant lipoprotein and has been used previously to express M. catarrhalis lipoproteins (3,11). The 1,967-bp oppA gene encoding the mature OppA protein was amplified from M. catarrhalis strain ATCC 43617 with primers P7 and P8 (Table 1) and ligated into pCATCH between restriction sites NcoI and BamHI.…”
mentioning
confidence: 99%